Innovativeness of micro and small enterprises – Are their innovation drivers different? - Bojan Jovanovski; Radmil Polenakovik; Ivana Stankovska; Trajce Velkovski; Bojan Jovanoski (Faculty of Technical Sciences, University of Novi Sad, 2020)
In the second half of the 20th century the labor cost, along with the level of in-dustrialization was considered to be the fundamental competitiveness factors. In today’s competitive business environment, innovation is the vital ability and ac-tivity for firm’s sustainability. Although the innovation is widely examined in the literature, further research is needed in this field to address which factors deter-mine the innovativeness of micro and small enterprises. The purpose of this re-search was to fill in that gap through development and implementation of a meth-odology for modelling of the innovativeness of micro and small enterprises. The first step is the analysis of the relevant literature and mapping two types of factors that are widely discussed: influencing factors – supporting innovation and influ-enced factors. The conceptual model that was developed based on these findings is refined through structured interviews of 18 experts from different stakeholders in the innovation ecosystem. The refined model is validated through 150 quantita-tive interviews with micro and small companies in the Northeast region of North Macedonia. Based on the validated model, the following factors are most influen-tial in the analyzed region: the openness of the company, the identification of the employees with the company, communication, owner’s profile, diversification in educational areas of employees and encouraging employees to propose innova-tion. The methodology and the models offer significant input into future research, as well in the development of analytical tools at the regional level, as well as for modelling of innovativeness on company level.
Keywords: Modelling Innovation, Innovation of micro and small enterprises, Factors of in-novativeness, Measuring innovativeness, Innovation ecosystem.